Studies on the Child Handbook in Brazil: a scoping review - Juliana Araujo Teixeira; Cintia de Freitas Oliveira; Maritsa Carla de Bortoli; Sonia Isoyama Venâncio (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To systematically identify and map studies involving the Caderneta da Criança (Child Handbook - CH) in Brazil. METHODS A scoping review using the methodology proposed by the Joanna Briggs Institute. The databases PubMed, Biblioteca Virtual em Saúde (BVS), Biblioteca Digital Brasileira de Teses e Dissertações, Periódicos Capes and Google Scholar were consulted. Primary and secondary studies that mentioned the use of CH were included, without restrictions regarding design, year of publication or population, published in Portuguese, English or Spanish and gray literature (theses and dissertations). RESULTS A total of 129 studies were included, mostly descriptive, published as scientific papers. The Northeast region, the population of caregivers of children and the Primary Care scenario were observed in most studies; 47% of the studies used the CH as a source of data, the majority on vaccination. Despite the different criteria to define adequacy of completing the CH, the studies identified weaknesses in filling out all of its items, except for immunization. The utilization and/or completion of the CH were linked to various factors, including the availability of the CH, characteristics of the children (such as sex, age, prematurity and well-child appointments), attributes of the family members and caregivers (such as age, education, income, parity, work status, prenatal care, reading, note-taking and bringing CH to appointments) and features of the professionals (such as workplace, medical specialty, communication style, knowledge about the CH, requesting, guiding and note-taking). CONCLUSIONS The results reinforce the need to better understand which factors affect the distribution of the CH in the population, as well as pointing to the need for understanding its use and completion by the different care points. The need for intervention studies to improve the implementation of this tool and to include training on the use of the CH in the context of continuing health education becomes evident.